PERFORMANCE ANALYSIS OF MOTIVATION, TRAINING, AND REWARD FACTORS (A Study of Teachers at UPTD SMP Negeri 2 Peudada, Bireuen Regency) - Nia Safira; M. Yusuf; Win Konadi; Rizkan Abqa (IndOmera, 2025)
This study aims to empirically prove the internal and external influences on strengthening teacher performance, based on the variables of motivation, training, and awards. Using a sample of 31 teachers as respondents who work at the UPTD of SMP Negeri 2 Peudada. Applying the path analysis model, the results obtained are: (1) Partially, the motivation, training, and awards factors influence the strengthening of teacher performance. (2) In the model of the relationship between factors, it is stated as Y = 0.558 + 0.585 X1 + 0.480 X2 + 0.430 X3 (X1: Motivation, X2: Training, X3: Awards, Y: Performance). And the three suspected variables significantly influence the teacher's performance. It was also found that the motivation factor has the largest contribution. (3) Simultaneously, the three variables have a significant influence on teacher performance with a contribution of 60.7 percent.